(untitled) (Web of Teachers: Inderscience Research, 2026)
The article explores the scientific, theoretical, and practical aspects of optimizing production processes at industrial enterprises through the application of digital technologies. The subject of the research is production management processes under conditions of industrial digital transformation, while the focus is on substantiating technical solutions aimed at improving the efficiency of production systems. The purpose of the study is to identify key problems inherent in traditional production management models, including equipment downtime, insufficient coordination of production operations, and inefficient resource utilization, as well as to determine ways to address these issues through digital technologies. The relevance of the research is driven by increasing requirements for competitiveness, sustainability, and performance of industrial production. The methodological framework is based on systems and comparative approaches, along with analytical interpretation of modern industrial digitalization concepts. The study shows that the implementation of digital technologies leads to increased labor productivity, reduced technological downtime, and optimization of production cost structures. The results can be used to improve management systems at industrial enterprises and to develop programs for phased digital modernization. The conclusions confirm the feasibility of comprehensive implementation of digital solutions, taking into account the technical and organizational characteristics of enterprises.